I am attempting to prove the equivalence of the following two definitions of distributive lattices:
$(a \lor b) \land c = (a \land c) \lor (b \land c)$
$(a \land b) \lor c = (a \lor c) \land (b \lor c)$
I haven't figured it out yet, but along the way I came up with this probably bogus proof:
$(a \lor b) \land c = (a \land c) \lor (b \land c)$
Renaming variables (rename b to c and c to b):
$(a \lor c) \land b = (a \land b) \lor (c \land b)$
Rename with $b = b \lor c$ (by noticing the left side of the equation looks like the right side of the second condition):
$(a \land c) \lor (b \land c) = (a \land (b \lor c)) \lor (c \land (b \lor c))$
Using the identities $b \land c = b \land c \land c$ and $c \lor (b \land c) = c$, simplify:
$(a \land c) \lor ((b \land c) \land c) = (a \land (b \lor c)) \lor c$
Now, here's the dodgy step. Once again, rename $b \lor c$ to $b$, which concludes the proof:
$(a \land b) \lor c = (a \lor c) \land (b \lor c)$
Where does this proof go wrong (or is it fine?), and what is the proof strategy for properly showing this equivalence?